Nutritional Characteristics of the Seed Protein in 23 Mediterranean Legumes - Elamine, Youssef (2022)
The search for new sources of plant protein for food and animal feed is driven by an increasing demand in developing countries and the interest in healthy alternatives to animal protein. Seeds from 23 different wild legumes belonging to tribes Gallegeae, Trifolieae, and Loteae were collected in southern Spain and their total amino acid composition was analyzed, by reverse phase-high performance liquid chromatography (RP-HPLC), in order to explore their nutritional value. Protein content in the seeds ranged from 15.5% in Tripodium tetraphyllum to 37.9% and 41.3% in Medicago minima and Medicago polymorpha, respectively. Species belonging to tribe Trifolieae, such as Melilotus elegans and Trifolium spp., showed the most equilibrated amino acid composition and the best theoretical nutritional values, although all species were deficient in sulfur amino acids. The amino acid composition of the seeds from some of these legumes was characterized by high levels of the anticancer non-proteic amino acid canavanine This amino acid was found free in the seeds from some of the species belonging to each of the three tribes included in the present work. Astragalus pelecinus in tribe Gallegea, Trifolium angustifolium in tribe Trifolieae, and Anthyllis vulneraria in tribe Loteae have 3.2%, 3.7%, and 7.2% canavanine, respectively. Seeds from Anthyllis vulneraria, Hymenocarpus lotoides, and Hymenocarpos cornicina have the highest contents in canavanine overall. In conclusion, the seeds from some of these legumes could be used for human consumption and for feeding animals because they contain protein of good nutritional quality. These plants could be useful in domestication and breeding programs for production of new varieties with improved nutritional and functional properties. In addition, some of these species may be of interest as a source of the bioactive compound canavanine